Transradial versus Transfemoral Approach in Peripheral Arterial Interventions - Oren, Ohad; Oren, Michal; Turgeman, Yoav (International Journal of Angiology, 2016)
This study aims to compare the clinical and procedural characteristics, including iatrogenic complications, of transradial versus transfemoral approach in patients who underwent peripheral arterial interventions.We retrospectively analyzed data of 72 patients who had undergone interventions of peripheral arteries in the preceding 3 years. Of all the procedures, 39 were performed using the transfemoral approach and 33 using the transradial approach. We assessed baseline clinical factors as well as procedure-related parameters (volume of contrast media, the amount of radiation, and duration of radiation exposure), rates of primary success, and acute vascular, access-site, or neurological complications.Patients whose interventions were done via transradial access had similar demographic characteristics to those who had transfemoral angioplasties. The presence of cardiovascular risk factors was similar in the two groups, but patients in the transradial subset were significantly more likely to have dyslipidemia (90.9 vs.71.7%, p value = 0.04) and less likely to have baseline chronic kidney disease (3.0 vs. 23.0%, p value = 0.01). The length of admission was shorter for patients who underwent transradial interventions compared with the transfemoral approach (1.1 vs. 1.3 days, p value = 0.04). Fluoroscopy time, the amount of radiation, and the volume of contrast media were similar between the two groups. Rates of primary success and periprocedural complications did not differ between the two groups.The transradial route appears to be a viable, safe, and noninferior alternative to the transfemoral approach for treatment of atherosclerotic stenosis in peripheral arterial territories. Prospective studies are needed.
Keywords: atherosclerosis; carotid stenosis; internal carotid artery; peripheral arterial disease; percutaneous; transradial coronary intervention; subclavian stenosis